AN EXAMINATIONS OF ALLEGATION OF NON-COMPLIANCE WITH AML/CFT LAWS AGAINST ISLAMIC BANKING - Maruf Adeniyi Nasir; Dato’ Ng See Teong (Jurnal Akta, 2021)
The dangerous dimension which the terrorism financing incursion introduced to peace and harmonious life globally makes the issue of money laundering and combatting financing terrorism (AML/CFT) a serious phenomenon. The compliance with the AML/CFT laws now generates global interest. Assessment of whether Islamic banks are complying with AML/CFT compliance measures becomes a grave issue that require attention particularly against the background of allegation by Western countries of lax control and supervision. This is probably because of the havoc that the world has continuously experienced as a result of this menace. The issue has continued to come in different dimensions and like a Siamese twin, the banks have become the focal point and inseparable in the issue of how to combat this menace. Incidentally, the increase in the growth and development of Islamic banks across the globe has dragged it to the centre of discussion. Thus, there have being a recurring issue on Islamic financial institutions regarding its compliance with Anti-money laundering laws and Combating Financing Terrorism (AML/CFT) measures. There were allegations of non-compliance with AMLCFT laws by Islamic banks, particularly by some Western countries led by the United States of America. Consequently,  the issue of combatting money laundering and terrorism has become a major issue in the global domain. This paper has extensively examined the allegation of non-compliance of Islamic banks with AML/ CFT laws. This is done by beaming searching light on the growing perception of lax in the control, monitoring, weak supervision, and non-compliance of Islamic banks with AML/CFT measures that is been spearheaded by some western countries, led by the US. Thus, by using the doctrinal research methodology, the paper sought to determine the veracity of the allegation and incidentally found that the allegation is not only baseless but lacks empirical evidence.